Characterization of the Meal-Stimulated Incretin Response and Relationship With Structural Brain Outcomes in Aging and Alzheimer’s Disease - Morris, Jill K.; John, Casey S.; Green, Zachary D.; Wilkins, Heather M.; Wang, Xiaowan; Kamat, Ashwini; Swerdlow, Russell S.; Vidoni, Eric D.; Petersen, Melissa E.; O’Bryant, Sid E.; Honea, Robyn A.; Burns, Jeffrey M. (Frontiers in Neuroscience, 2020)
Background. Individuals with Alzheimer’s Disease (AD) are often characterized by systemic markers of insulin resistance; however, the broader effects of AD on other relevant metabolic hormones, such as incretins that affect insulin secretion and food intake, remains less clear. Methods. Here, we leveraged a physiologically relevant meal tolerance test to assess diagnostic differences in these metabolic responses in cognitively healthy older adults (CH; n=32) and AD (n=23) participants. All individuals also underwent a comprehensive clinical examination, cognitive evaluation, and structural magnetic resonance imaging. Results. The meal-stimulated response of glucose, insulin, and peptide tyrosine tyrosine (PYY) was significantly greater in individuals with AD as compared to CH. Voxel-based morphometry revealed negative relationships between brain volume and the meal-stimulated response of insulin, C-Peptide, and glucose-dependent insulinotropic polypeptide (GIP) in primarily parietal brain regions. Conclusion. Our findings are consistent with prior work that shows differences in metabolic regulation in AD and relationships with cognition and brain structure.